2022
DOI: 10.1101/2022.01.26.22269913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain network mechanisms of visual perceptual organization in schizophrenia and bipolar disorder

Abstract: Visual shape completion is a canonical perceptual process that integrates spatially distributed edge information into unified representations of objects. People with schizophrenia show difficulty in discriminating completed shapes but the brain networks and functional connections underlying this perceptual difference remain poorly understood. Also unclear is whether similar neural differences arise in bipolar disorder or vary across the schizo-bipolar spectrum. To address these topics, we scanned (fMRI) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
(241 reference statements)
1
1
0
Order By: Relevance
“…Our results showed that FDI could be a promising feature to be used in classifiers based on EEG measures, especially when computed for the SAN network (AUC = 0.83). These results reinforce the hypothesis that cognitive networks—but not visual networks—would be differentially active in schizophrenia ( Keane et al, 2022 ). Moreover, FDI as a feature could add a broader perspective when analyzing complexity in current machine learning classifiers which are based on linear and non-linear measures computed directly on the EEG signal, because the input EEG signal is used in FDI to extract the brain activations over time, which allows for analyzing 3D and 4D complexity through fractal dimension.…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that FDI could be a promising feature to be used in classifiers based on EEG measures, especially when computed for the SAN network (AUC = 0.83). These results reinforce the hypothesis that cognitive networks—but not visual networks—would be differentially active in schizophrenia ( Keane et al, 2022 ). Moreover, FDI as a feature could add a broader perspective when analyzing complexity in current machine learning classifiers which are based on linear and non-linear measures computed directly on the EEG signal, because the input EEG signal is used in FDI to extract the brain activations over time, which allows for analyzing 3D and 4D complexity through fractal dimension.…”
Section: Discussionsupporting
confidence: 86%
“…The spectral signatures related to the processing of visual information are altered in people living with schizophrenia (Sz) (Green et al, 2003 ; Spencer et al, 2003 , 2004 , 2008 ; Wynn et al, 2005 ; Uhlhaas et al, 2006 ; Grützner et al, 2013 ). Notably, these changes are accompanied by changes in visual processing (Dakin et al, 2005 ; Kantrowitz et al, 2009 ; Horton and Silverstein, 2011 ; Keane et al, 2014 , 2022 ; Schallmo et al, 2015 ), and visual aberrations are related, even prodromally, to the severity of clinical symptoms (Phillipson and Harris, 1985 ; Uhlhaas and Mishara, 2007 ; Keane et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%